Tax policy and human capital formation with public investment in education - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
This paper studies the eects of distortionary taxes and public in- vestment in an endogenous growth OLG model with knowledge trans- mission. Fiscal policy aects growth in two respects: .rst, work time reacts to variations of prospective tax rates and modi.es knowledge formation; second, public spending enhances labour e ciency but also stimulates physical capital through increased savings. It is shown that Ramsey-optimal policies reduce savings due to high tax rates on young generations, and are not necessarily growth-improving with respect to a pure private system. Non-Ramsey policies that shift the burden on adults are always growth-improving due to crowding-in eects: the welfare of all generations is unambiguously higher with respect to a private system, and there generally exists a continuum of non-optimal tax rates under which long-run growth and welfare are higher than with the Ramsey-optimal policy.
Keywords: E62; O41; O11; 330; Endogenous growth; Human capital; Overlapping generations; Tax policy; Public investment; Endogenes Wachstumsmodell; Humankapital; Overlapping Generations; Steuerpolitik; Öffentliche Investition; Bildungspolitik